The Economy as a Complex Spatial System: Macro, Meso and Micro Perspectives - Commendatore, Pasquale; Kubin, Ingrid; Bougheas, Spiros; Kirman, Alan; Kopel, Michael; Bischi, Gian Italo (Springer Proceedings in Complexity, 2017)
economic geography; systemic risk; heterogeneous agents; complex networks analysis; multinational enterprises; spatial econometrics; COST Action IS1104